A legal framework with scientific basis for applying the ‘polluter pays principle’ to soil conservation in rural watersheds in Brazil - Valera, C. A. [UNESP]; Pissarra, T. C.T. [UNESP]; Martins Filho, M. V. [UNESP]; Valle Junior, R. F.; Sanches Fernandes, L. F.; Pacheco, F. A.L. (Elsevier, 2017)
The “polluter pays principle” (PPP) has been looked at from the perspective of legal values and technical principles, namely of soil science, to evaluate the acceleration of soil erosion and the consequent development of degraded areas in the Uberaba River basin (area: 2419 km2), state of Minas Gerais, Brazil. Having accomplished this goal, the study highlights the importance of PPP for the conservation of soil and development of an ecologically equilibrated environment. The diagnosis of degraded areas was based on the coupling of a Geographic Information System with soil loss, land use conflict and tolerance to soil loss models, and revealed a preoccupying situation because an extension of approximately 905 km2 (1/3 of the basin) has been considered in advanced state of degradation potentially causing environmental damage (e.g., decline of soil fertility and hence crop production, negative impacts of soil particles export on stream and lake water quality and biodiversity of riverine ecosystems). Facing this problem, a legal framework standing on doctrinaire principles, federal laws and the Brazilian Constitution has been proposed whereby the protagonists of soil degradation are called to assume responsibility as well as the costs of repairing this negative condition. Although the study has been carried out on a specific country under pre-defined settings, the rationale behind the proposals can easily be transposed to other scenarios because the scientific methods on which soil degradation has been defined and mapped are generally applicable, while the suggested legal values are currently applied to many regions on the planet.
Keywords: Degraded area; Environmental damage; Geographic information system; Law; Legal responsibility; Soil erosion